Challenges in Learning Legal English from Students' perspective at Hanoi Law University - Nhac, Huong Thanh ((JELE) Journal Of English Language and Education, 2021)
Legal English, also known as Language of the Law (Mellinkoff, D. 2004), is an indispensable factor contributing to the development of legal field. At Hanoi Law University, Legal English is a compulsory subject in the syllabus of legal English majors and International Trade Law majors. The question that what obstacles students face when dealing with legal English, however, has not been fully answered at that institution. This present research, which makes use of survey questionnaires as the main method, aims to study the challenges of learning legal English from the students’ perspective. The results indicate notable difficulties arising from the distinctive characteristics of legal English, differences in legal systems between countries and insufficient background knowledge of the laws. It is expected that these findings do propose a number of practical recommendations in order to improve the effectiveness of learning legal English among students as well as the methods of teaching legal English among teachers.